2018
DOI: 10.1021/acs.joc.8b01249
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azolo[1,3,5]triazines via Rhodium(III)-Catalyzed Annulation of N-Azolo Imines and Dioxazolones

Abstract: A wide range of azolo[1,3,5]triazines were obtained by Rh(III)-catalyzed annulation of N-azolo imines and dioxazolones. The reaction proceeds by the first catalytic C-H amidation of an imidoyl C-H bond followed by cyclodehydration. Good yields were obtained for N-azolo imines derived from aminoazoles and aromatic and heteroaromatic aldehydes. A range of dioxazolone amidating reagents were employed to introduce aryl, heteroaryl, and alkyl substituents. The reaction was also performed with a benchtop setup at 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…40 Work from Chang and others showed these dioxazolone reagents can facilitate various metal-catalyzed C-H amidation and alkene functionalization reactions. [41][42][43][44][45][46][47][48][49][50][51][52][53] Recently, we discovered dioxazolones can undergo intermolecular N-N coupling with arylamines to make hydrazides under either iridium or iron catalysis. [54][55][56][57][58][59][60][61][62][63][64] Mechanistic studies of the Ir-catalyzed system indicated an outer-sphere nucleophilic attack of the nitrogen group of Ir-nitrenoid intermediate by amine leads to the N-N coupling product.…”
Section: Resultsmentioning
confidence: 99%
“…40 Work from Chang and others showed these dioxazolone reagents can facilitate various metal-catalyzed C-H amidation and alkene functionalization reactions. [41][42][43][44][45][46][47][48][49][50][51][52][53] Recently, we discovered dioxazolones can undergo intermolecular N-N coupling with arylamines to make hydrazides under either iridium or iron catalysis. [54][55][56][57][58][59][60][61][62][63][64] Mechanistic studies of the Ir-catalyzed system indicated an outer-sphere nucleophilic attack of the nitrogen group of Ir-nitrenoid intermediate by amine leads to the N-N coupling product.…”
Section: Resultsmentioning
confidence: 99%
“…Hogan et al . in 2018, synthesized azolo‐ s ‐triazine analogue P21 through rhodium (III) catalysed annulations of N ‐azolo imines and dioxazolones [27] . In first step of reaction catalytic C−H amidation of an imidoyl C−H bond is observed which later undergoes cyclodehydration.…”
Section: Synthesismentioning
confidence: 99%
“…As we all know,C O [1] and isocyanides [2] are good onecarbon components due to their carbon atoms having carbenic character,a nd they have been extensively investigated for over ac entury.1 -Sulfonyl-1,2,3-triazoles are also useful synthons [3] that can be transformed into metal-bound iminocarbene intermediates. Subsequently,t hese intermediates can generate heterocycles via various transannulation reactions.I na ddition,a lkynes, [4] alkenes, [5] sulfoxonium ylides, [6] and dioxazolones [7] have been reported as synthons to achieve the synthesis of nitrogen heterocycles catalyzed by transitionm etals.B ecause diazo compounds possess the similar characteristico fb eing electron-deficient, they have been used as carbene precursors to prepare ortho-functionalized arenes bearing various directing groups.I nc ombination of intramolecular tandem cyclization reactions,awide range of nitrogen heterocycles can be accessed, such as indoles, indolines,i soquinolines,i soquinolones,a nd so on. Recently,g reat progress has been made in synthesis of nitrogen heterocycles via transitionm etal-catalyzed C-H activation/carbene insertion/intramolecular annulation sequences using diazo compoundsa sc oupling partners.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, these intermediates can generate heterocycles via various transannulation reactions. In addition, alkynes, alkenes, sulfoxonium ylides, and dioxazolones have been reported as synthons to achieve the synthesis of nitrogen heterocycles catalyzed by transition metals. Because diazo compounds possess the similar characteristic of being electron‐deficient, they have been used as carbene precursors to prepare ortho ‐functionalized arenes bearing various directing groups.…”
Section: Introductionmentioning
confidence: 99%